Care at the first postnatal hour in two hospitals of the Adequate Birth Project: qualitative analysis of experiences in two stages of the Healthy Birth research - Maysa Luduvice Gomes; Lucia Regina de Azevedo Nicida; Débora Cecília Chaves de Oliveira; Andreza Rodrigues; Jacqueline Alves Torres; Amanda da Trindade Dias Coutinho; Beatriz da Silva Soares de Souza Cravo; Juliana Guimarães Dantas; Thays Basílio Oliveira; Patrick Brandão; Rosa Maria Soares Madeira Domingues (BMC, 2023)
Plain language summary This study aims to analyze the care model of the first postpartum hour offered by two hospitals participating in the Adequate Childbirth Project (PPA), a quality improvement project to enhance normal delivery and reduce unnecessary cesarean sections in Brazilian private hospital. It is a qualitative analysis, based on the narrative of 102 women attended at two hospitals participating in the PPA. Categories that emerged from the analysis: "First hour; dimension of time and care expressed in the lived experience" and "Interferences in care in the first hour of life". Most women expressed a chronological time of skin-to-skin contact far from the ideal recommended in the first postpartum hour; however, they valued the experience and its meaning. Two barriers were observed in this care process: the interruption of skin-to-skin contact for neonatal care and the transfer to the recovery room, without observing the duration of the "golden hour". We can conclude that women evaluated the service positively, with indications that point to the sustainability of the PPA. Information during antenatal care to increase women´s autonomy are needed to improve the implementation of these practices and access to their health benefits.